(untitled) (Global Journal of Management and Business Research, 2022)
Capital Structure is an important concept in business which have accounted for financial performance of businesses in literature. Thus, this study was conducted to examine the relationship between capital structure and financial performance of commercial banks in Nigeria for the period of (2010 to 2019). Five (5) commercial banks were selected using Judgmental sampling technique. Data were collected from financial statements of selected banks. The data was analyzed using E-View 2010. Unit root test, Granger causality test and panel regression Analysis was conducted in this study. We concluded that, capital structure variables used are good predictor and significant with financial performance of commercial banks in Nigeria. In addition, we concluded that, Debt to Equity Ratio, Total Debts and Total Equity over the period under study, do not contributed to the financial performance (Return on Assets) of commercial banks in Nigeria. Furthermore, Equity to Capital Ratio and Debts to Capital Ratios improves the financial performance(Return on Assets) of commercial banks over the years. We therefore, recommended that, the bank managers should ensure that, capitals are spent on productive assets in other to improve financial performance of the banks, among others.